PENGARUH PERSPEKTIF MODERNIS TERHADAP PERILAKU NASIONALISME PADA SISWA SMA NEGERI 1 BANTAN - Rohmah, Zainur Rohmah; ', Hambali; ', Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study background of the lack of a sense of nationalist, students forget the identity of his own nation, more individualistic and hedonism. This is because students are not able to filter out the influence of modernization that has penetrated into every aspect of life. So writer take the title